PERAN GENDER EGALITARIAN DAN INTENSI SUAMI MELAKUKAN KEKERASAN TERHADAP ISTRI DI KELURAHAN TLOGOSARI KULON, PEDURUNGAN, SEMARANG - Sugeng Supriyono (Widyariset, 2009)
The numbers of wife abuse increased because offamily crisis and the beginning ofmarital problem. The aim of this research was to analyze the correlation between egalitarian role gender with wife abuse. Samples (N=60) were married husbands for 1-11 years, with range of age 27-40 years old, with kids, no nannies and living at Tlogosari Kulon Pedurungan Semarang. This research was carried out by using purposive sampling. Data were collected throughout scale and statistical regresion analysis. The result showed a significant correlation between egalitarian role gender with wife abuse with R Square = 0,334 at significance of 0,00 (p<0,01). It meant that high lower of intense hardness to wife, that equaled to 33,4 %, was determined by egalitarian role gender.